Jamur Mikoriza Vesikular Arbuskular (MVA) pada Tiga Jenis Tanah Rhizosfer Tanaman Pisang Nipah (Musa paradisiaca L. var. nipah) Di Kabupaten Pontianak - Irwan Lovadi, Bayu Saputra, Riza Linda (Jurnal Protobiont, 2015)
The growth rate of banana (M. paradisiaca L. var. nipah) in three types of soil in Pontianak district is very high. The plant growth is expected to be affected by vesicular arbuscular mycorrhiza’s activity, a type of fungus that helps the process of growth and absorption of nutrients from its surroundings. This study aims todetermine the Genus found in vesicular arbuscular mycorrhiza and percentage of infection level in three types of soil planted with banana (M. paradisiaca L. var. nipah). This study was carried out for three months from April 2014 to June 2014 in Laboratory of Microbiology, Faculty of Mathematics and Natural Sciences,University of Tanjungpura. The procedure in this study consisted of several stages, namely sampling, isolation of spores with combination method, pour-wet filter technique and centrifugation technique, identification and characterization, as well as coloring and making root preparations with method of coloring. Based on observation result at Genus spores of vesicular arbuscular mycorrhiza in alluvial soil, Acaulospora, Archaeospora, Gigaspora, Glomus and Paraglomus were found. Genus spores of vesicular arbuscular mycorrhiza can be found in peat soil that contained Archaeospora, Gigaspora, Glomus, Paraglomus and Scutellospora. In ultisol soil, Genus spores of vesicular arbuscular mycorrhiza consisted of Acaulospora, Gigaspora, Glomus and Paraglomus. Observation result on vesicular arbuscular mycorrhiza indicated that the percentage of infection in alluvial soil was 53% (high), 41% (average) in peat soil and ultisol soilamounted 57% (high).